Single image enhancement in various weather conditions using Intensity and Saturation Deterioration Ratio - Alajarmeh A.; Salam R.A.; Marhusin M.F.; Khairi Abdul Rahim (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/ Scopus